The Strategic Role of Local Political Parties in the Legislative Process Qanun for Sharia Financial Institutions in Aceh - Alqarni, Wais; Saleh, Rahmat; Anggraini, Titi; Sulaksono, Tunjung; Akhyar, M. Nur (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
According to the 2019 Election data, the Aceh Party secured 18 out of the 81 seats in the Aceh DPR (Legislative Assembly). The Speaker of the DPR is appointed from the Aceh Party, which holds the majority of seats in the legislature as the winners of the election. Furthermore, Commission I is responsible for overseeing matters related to Law, Politics, Government, and Security, is headed by a member of the DPR representing the Aceh Party. The Aceh DPR Legislation Body is led by a member of the Aceh DPR who belongs to the Aceh Party. This study employs a qualitative-normative approach, utilizing role theory for analysis. Data is gathered through in-depth interviews and literature review. The participants interviewed consisted of individuals affiliated with the DPR, the Islamic Sharia Service, and Academics. The material studied encompassed journal papers, books, news media reports, and research relevant to the topic under consideration. The findings suggest that local parties play a significant influence in the enactment of the LKS Qanun. The Aceh Party, a local political organization, emerged victorious in the election and secured the majority of seats in the Aceh parliament. This is evident through the participation of the chairman of the Aceh DPR legislative body who originates from the Local Party. This is an important part of the Political Party's contribution to the development of local democracy in Aceh as well as supporting the implementation of Islamic law in Aceh based on law within the framework of the unitary state of the Republic of Indonesia.